(untitled) (GEOMATE Journal, 2019)
Ground anchor systems (also known as earth anchor systems) are installed to stabilize structures or slopes by connecting a structure or a slope to the anchorage zone using the frictional force between grouting material and surrounding ground. However, the pullout resistance of anchors decreases over long periods of time, causing the anchor to finally pulled out from the ground owing to the decreasing friction between grouting material and surrounding ground. An open-wing type (OW) anchor has been developed by our research group as a new type of earth anchor system to address the issues associated with the currently existing methods. The method uses open wings to exert the pullout resistance. Our research group conducts experiments to examine the effects of a number of wings, root depth, and type of ground on the pullout resistance exerted by OW anchors. The experimental results show the reduction rate of maximum pullout resistance exerted by OW anchor compared to that exerted by disk does not change with the values of relative density and root depth under similar ground conditions.In this study, a formula to calculate the pullout resistance exerted by OW anchor is proposed. The developed formula is based on the formula used for calculating the maximum pullout resistance exerted by a disk as an earth anchor model. The proposed formula relies on the results of experiments to evaluate the pullout resistance exerted by OW anchor.